The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pone.0278871
|View full text |Cite|
|
Sign up to set email alerts
|

Contrast of oropharyngeal leak pressure and clinical performance of I-gel™ and LMA ProSeal™ in patients: A meta-analysis

Abstract: Background Conflicting outcomes have been reported for the i-gel™ and laryngeal mask airway (LMA) ProSeal™ in children and adults during general anesthesia. Randomized controlled trials (RCTs) that yielded wide contrast outcomes between i-gel™ and LMA ProSeal™ were included in this meta-analysis. Methods Two authors independently identified RCTs that compared i-gel™ with LMA ProSeal™ among patients receiving general anesthesia by performing searches in EMBASE, Cochrane, PubMed, and ScienceDirect. Discussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Similar to the results of our study, most previous studies on i-gel have shown first attempt success and overall insertion rates close to 90%–100%. [ 5 6 9 ] Previous study on BlockBuster™ has also claimed 96% first attempt success rates which is similar to our result. [ 6 10 ] Easier insertion and high first pass success can be possibly explained by the structural analysis of BlockBuster™, which has an inflatable cuff and an angulated (95°) airway tube which matches oropharyngeal curve and provides easy insertion without even using finger to guide the device into the mouth of the patient.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the results of our study, most previous studies on i-gel have shown first attempt success and overall insertion rates close to 90%–100%. [ 5 6 9 ] Previous study on BlockBuster™ has also claimed 96% first attempt success rates which is similar to our result. [ 6 10 ] Easier insertion and high first pass success can be possibly explained by the structural analysis of BlockBuster™, which has an inflatable cuff and an angulated (95°) airway tube which matches oropharyngeal curve and provides easy insertion without even using finger to guide the device into the mouth of the patient.…”
Section: Discussionsupporting
confidence: 92%